2014
DOI: 10.1016/j.yebeh.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and costs in children with stable and uncontrolled epilepsy

Abstract: Children with uncontrolled epilepsy use significantly more healthcare resources and have a greater economic burden than children with stable epilepsy. However, epilepsy accounted for only half of overall costs, indicating that comorbid conditions may add substantially to the disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 25 publications
4
70
1
Order By: Relevance
“…32 First-year health care charges did not differ across any other clinical or demographic factors. These findings are consistent with previous studies, 10,11,27 with the exception of medication adherence. 34,35 Discrepant findings are likely due to adherence measurement methods, which were prescription refill data in the adult studies and self or caregiver report, which is known to be inflated, in the current study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…32 First-year health care charges did not differ across any other clinical or demographic factors. These findings are consistent with previous studies, 10,11,27 with the exception of medication adherence. 34,35 Discrepant findings are likely due to adherence measurement methods, which were prescription refill data in the adult studies and self or caregiver report, which is known to be inflated, in the current study.…”
Section: Resultssupporting
confidence: 93%
“…10 Thus, we aimed to describe the health care utilization patterns and inpatient and outpatient charges in the 12 months following a pediatric epilepsy diagnosis, estimate average annual perpatient health care charges, and identify demographic, clinical, and psychosocial predictors of total health care charges. In line with previous studies, we hypothesized that seizure occurrence, AED nonadherence, and poor HRQOL among youth with newly diagnosed epilepsy would predict increased health care charges in the 12 months postdiagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric epilepsy patients have significant medical costs, 11 and there is significant variation across institutions in how care for these patients is delivered. 12 Some studies have shown that increased education can improve understanding of epilepsy 4 and that lay-education programs can improve health and reduce hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of epilepsy is devastating and includes social and medical morbidity of the disorder and where epileptic patients are greatly stigmatized and frequently untreated, particularly in developing countries. Epilepsy adversely affects childhood development and could lead to increased economic burden in pediatric populations 8. Hence, the inclusion of Zn supplements into the treatment regimen of pediatric epilepsy is solicited to be economically profitable because it allows to improve the quality of life of epileptic children, minimizes the costs of frequent hospital visits and recurrent hospitalizations, and maintains foreseeable manpower resources.…”
mentioning
confidence: 99%